(untitled) (Medical Forum Monthly, 2024)
Objective: To explore the perception of students about utilization of self-study time. To explore the factors influencing the student's attitude towards utilization of self-study hours. Study Design: An observational / descriptive / cross-sectional study Place and Duration of Study: This study was conducted at the Islamic International Medical College (IIMC) from June 2019 to December 2019. Materials and Methods: 20 statement Structured questionnaire containing 12 questions related to perception of students about utilization self-study and 4 questions on factors like self-study resources, time and place given to it. Data was analyzed by SPSS 21 version. Results: Two hundred and seventy students participated in the survey (Response Rate = 76%). Mean value for perception of students about utilization of self-study hour was 3.10 (SD=1.32) and the mean of factors affecting this perception was 2.66 (SD=1.30). 58% of students said that self-study enhanced their learning abilities and it should be placed before small group discussions (72%). Factors affecting the utilization of self-study hours are resources, venues, placement of self-study hours in time table, total time given per module and guidance are the important factors. Conclusion: Students perceive self-study as useful component for learning but most of them are not utilizing it in study purposes due to lack of resources. Analysis of results find that the effect of self-study on academic success depends on providing calm and resourceful venues with better distribution of hours in schedule with some motivation and supervision.